Analysis of expressed sequence tags derived from inflorescence shoot of Tectona grandis (teak) - Haron, Mohd Rosli; Mohd Saleh, Norihan; Mohd Noor, Mohd Iqbal; Muhammad, Norwati; Basherudin, Norlia; Adnan, Norwati (Academic Journals, 2009)
Teak Inflorescence Shoot Stage 4 (TIS4) shoots bearing the floral meristems were used to construct a cDNA librariy with insert size range of 1500 - 5000 bp. The titer of the library was 7.5 x 105 pfu/ml (primary) and 4.5 x 109 pfu/ml (amplified). EST generation and analysis were performed using the cDNA library where a total of 1384 plaques were randomly picked and their inserts PCR-amplified using T3 and T7 universal primers. Only 1125 plaques generated single amplified fragments, each which were purified and sequenced using the SK universal primer. The generated raw 5’ ESTs were filtered and clustered. A total of 674 nonredundants (69 consensus sequences and 605 singletons) were generated and their identities searched through BLASTX. Of the 674 nonredundants, 107 of them (15.9%) showed no hits or no identity. All the 567 nonredundants identified through BLASTX were categorized into their functional categories and were further analysed using InterProScan to detect their protein signatures and to assign their GO numbers. From all the sequences analysed, only 186 (32.8%) sequences were given the GO numbers and grouped into the three GO main categories namely biological process, cellular component and molecular function. Several important ESTs were highlighted based on their functional categories. There were five sequences found to be related to flowering and light induction.